A black talc whitening composite powder and preparation method thereof

Through crushing, dry grinding, wet grinding, mechanical chemical coating and post-treatment steps, black talc whitening composite powder was prepared, solving the problems of low utilization rate and high energy consumption of black talc mineral resources, significantly improving The whiteness and resource utilization of black talc have expanded its application range and meet the requirements of energy conservation and environmental protection.

CN116355441BActive Publication Date: 2025-02-11JIANGXI GUANGYUAN CHEM +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310312945.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-02-11
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

The existing black talc mineral resource utilization rate and high energy consumption limit its application in materials with high whiteness and color requirements.

Method used

Black talc whitening composite powder was prepared by crushing, dry grinding, wet grinding, mechanical force chemical coating and post-treatment steps. This method uses liquid phase mechanical force chemistry to coat titanium dioxide on the surface of black talc powder to reduce static repulsion, promote coating, and significantly increase the whiteness of black talc.

Benefits of technology

It significantly improves the whiteness of black talc, expands its application range in industries such as coatings, white appliance modified plastics, white or colored cables, and reduces energy consumption, improves resource utilization, and meets the requirements of energy conservation and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116355441B_ABST
    Figure CN116355441B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fine chemicals, and discloses a black talc whitening composite powder and a preparation method thereof. The method of the present invention comprises the following steps: the raw black talc ore is crushed and dry-ground to obtain black talc powder; the black talc powder is mixed with water, formulated into a powder slurry, and constant temperature wet grinding is carried out after mixing with a grinding aid and a dispersant to obtain a black talc slurry; the black talc slurry is mixed and ground with titanium dioxide slurry and a flocculant, and liquid phase mechanochemical coating is carried out to obtain a core-shell composite slurry; the core-shell composite slurry is flash dried, depolymerized and broken up to obtain a black talc whitening composite powder. The above method of the present invention significantly improves the whiteness of black talc, expands the application field of black talc, can be whitened without high energy consumption, improves the resource utilization rate of black talc, and meets the requirements of energy conservation and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fine chemical industry, and in particular to a black talc whitening composite powder and a preparation method thereof. Background Art

[0002] my country has rich reserves of black talc resources and excellent quality, but its natural whiteness is only about 60% or even lower, which greatly limits the wide application of black talc. It can only be used in low-end industries that do not require color, such as black rubber, black cable, black modified plastics and other industries. In order to expand the application field of black talc and enable it to be used in some material fields that require whiteness and color, such as coatings, white household appliances modified plastics, white or colored cables and other industries, the existing process is to calcine black talc at 800-1300℃ to remove organic matter and free carbon in the original ore to improve its whiteness. Some studies believe that carbon can be completely removed at 750℃, but after calcining the carbon in black talc at 750℃ for 1h, there is still 0.17% carbon residue, and until 1200℃ talc Mg3[Si4O 10 ]The carbon basically disappears only after (OH)2 is completely decomposed. This method results in low utilization rate of black talc mineral resources, high energy consumption and high utilization cost.

[0003] Therefore, how to provide a black talc whitening method with high utilization rate, energy saving and environmental protection has important resource utilization value. Summary of the invention

[0004] The purpose of the present invention is to provide a black talc whitening composite powder and a preparation method thereof, so as to solve the problems of low utilization rate and high energy consumption of existing black talc mineral resources.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0007] (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then dry ground to obtain black talc powder;

[0008] (2) Wet grinding: mixing black talc powder with water to prepare a powder slurry with a solid content of 60-70%; mixing the powder slurry with a grinding aid and a dispersant and then performing constant temperature wet grinding to obtain a black talc slurry;

[0009] (3) Mechanochemical coating: black talc slurry, titanium dioxide slurry and flocculant are mixed and ground, and liquid phase mechanochemical coating is performed to obtain a core-shell composite slurry;

[0010] (4) Post-treatment: The core-shell composite slurry is flash dried, depolymerized and dispersed to obtain a black talc whitening composite powder.

[0011] Furthermore, in the preparation method of the black talc whitening composite powder, in step (2), the grinding aid is a mixture of polyethylene glycol and calcium lignin sulfonate, the amount of polyethylene glycol is 3 to 5‰ of the mass of the black talc powder, and the amount of calcium lignin sulfonate is 4 to 6‰ of the mass of the black talc powder.

[0012] Furthermore, in the preparation method of the black talc whitening composite powder, in step (2), the dispersant is a mixture of sodium methylene dinaphthalene sulfonate and sodium dodecylbenzene sulfonate, the amount of sodium methylene dinaphthalene sulfonate is 4 to 6‰ of the mass of the black talc powder, and the amount of sodium dodecylbenzene sulfonate is 3 to 5‰ of the mass of the black talc powder.

[0013] Furthermore, in the preparation method of the black talc whitening composite powder, in step (2), the rotation speed of the constant temperature wet grinding is 2500-3000 r / min, the time of the constant temperature wet grinding is 1-3 h, and the temperature of the constant temperature wet grinding is 70-80°C.

[0014] Furthermore, in the preparation method of the black talc whitening composite powder, in step (3), the solid content of the titanium dioxide slurry is 30-40%, the average particle size of the titanium dioxide powder in the titanium dioxide slurry is 0.1-0.3 μm, and the mass ratio of the titanium dioxide slurry to the black talc slurry is 1:30-50.

[0015] Furthermore, in the preparation method of the black talc whitening composite powder, in step (3), the flocculant is a mixture of polyacrylamide and sodium polystyrene sulfonate, the mass ratio of polyacrylamide to sodium polystyrene sulfonate is 0.8 to 1.2:1, and the amount of the flocculant is 2 to 4‰ of the mass of titanium dioxide in the titanium dioxide slurry.

[0016] Furthermore, in the method for preparing the black talc whitening composite powder, in step (3), the rotation speed of the mixed grinding is 300-600 r / min, the time of the mixed grinding is 1-3 h, and the temperature of the mixed grinding is 80-90°C.

[0017] The invention also provides a method for preparing a black talc whitening composite powder and a black talc whitening composite powder obtained.

[0018] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention utilizes liquid phase mechanochemical action to coat titanium dioxide on the surface of black talc powder during the stirring and grinding process, and adds a flocculant during the grinding process, which can reduce the electrostatic repulsion between powders and promote the coating of powder particles. Compared with the existing calcination whitening, the whiteness of black talc is significantly improved, and it can also be used in some material fields with requirements on whiteness and color, such as coatings, white household appliance modified plastics, white or colored cables and other industries, thereby expanding the application field of black talc, and whitening can be achieved without high energy consumption, thereby improving the resource utilization rate of black talc and meeting the requirements of energy saving and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0021] Figure 1 The process flow chart of the preparation method of the black talc whitening composite powder of the present invention;

[0022] Figure 2 This is a SEM image of the product of Example 1 of the present invention magnified 2000 times;

[0023] Figure 3 This is a SEM image of the product of Example 1 of the present invention magnified 5000 times. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0025] (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then sent to a 198-type ring roller mill for dry grinding to obtain 400-mesh black talc powder;

[0026] (2) Wet grinding: 400 mesh black talc powder is mixed with water to prepare a powder slurry with a solid content of 60-70%; the powder slurry is mixed with a grinding aid and a dispersant and then fed into a 3600L vertical stirred mill for constant temperature wet grinding to obtain a 5000 mesh black talc slurry;

[0027] (3) Mechanochemical coating: 5000 mesh black talc slurry, titanium dioxide slurry and flocculant were mixed and ground, and liquid phase mechanochemical coating was performed to obtain a core-shell composite slurry;

[0028] (4) Post-treatment: The core-shell composite slurry is flash dried, depolymerized and dispersed, collected in bags, and packaged as a finished product to obtain a black talc whitening composite powder;

[0029] In post-processing, the specific steps are:

[0030] Flash drying: The core-shell composite slurry is pumped into a rapid flash dryer and flash dried using clean hot air;

[0031] Deagglomeration and dispersion: The collected powders are fed into the deagglomeration and dispersion machine through a spiral reamer feeder to disintegrate the agglomerated powders and maintain the particle size of the original particles;

[0032] Bag collection: collect the dried powder through bags;

[0033] Finished product packaging: The powder after high-speed stirring is packaged by an automatic packaging machine.

[0034] In the present invention, the solid content of the powder slurry in step (2) is preferably 60-70%, more preferably 64-68%, and more preferably 65%.

[0035] In the present invention, the grinding aid in step (2) is preferably a mixture of polyethylene glycol and calcium lignin sulfonate.

[0036] In the present invention, the amount of polyethylene glycol used is preferably 3-5‰ of the mass of black talc powder, more preferably 4.5-5‰, and more preferably 5‰.

[0037] In the present invention, the amount of calcium lignin sulfonate is preferably 4-6‰ of the mass of black talc powder, more preferably 5-6‰, and more preferably 6‰.

[0038] In the present invention, the dispersant in step (2) is preferably a mixture of sodium methylene dinaphthalene sulfonate and sodium dodecylbenzene sulfonate.

[0039] In the present invention, the amount of sodium methylene dinaphthalene sulfonate is preferably 4-6‰ of the mass of black talc powder, more preferably 4.8-6‰, and more preferably 6‰.

[0040] In the present invention, the amount of sodium dodecylbenzene sulfonate used is preferably 3-5‰ of the mass of black talc powder, more preferably 4.2-5‰, and more preferably 5‰.

[0041] In the present invention, the rotation speed of the constant temperature wet grinding in step (2) is preferably 2500-3000 r / min, more preferably 2730-2950 r / min, and more preferably 2850 r / min.

[0042] In the present invention, the constant temperature wet grinding time in step (2) is preferably 1 to 3 hours, more preferably 1.5 to 2.2 hours, and more preferably 2 hours.

[0043] In the present invention, the temperature of the constant temperature wet grinding in step (2) is preferably 70-80°C, more preferably 72-76°C, and more preferably 75°C.

[0044] In the present invention, the solid content of the titanium dioxide slurry in step (3) is preferably 30-40%, more preferably 33-38%, and more preferably 35%.

[0045] In the present invention, the average particle size of the titanium dioxide powder in the titanium dioxide slurry in step (3) is preferably 0.1 to 0.3 μm, more preferably 0.18 to 0.25 μm, and even more preferably 0.2 μm.

[0046] In the present invention, the mass ratio of the titanium dioxide slurry to the black talc slurry in step (3) is preferably 1:30-50, more preferably 1:35-42, and more preferably 1:40.

[0047] In the present invention, the flocculant in step (3) is preferably a mixture of polyacrylamide and sodium polystyrene sulfonate.

[0048] In the present invention, the mass ratio of the polyacrylamide to sodium polystyrene sulfonate is preferably 0.8 to 1.2:1, more preferably 0.9 to 1:1, and more preferably 1:1.

[0049] In the present invention, the amount of the flocculant in step (3) is preferably 2-4‰ of the mass of titanium dioxide in the titanium dioxide slurry, more preferably 3.2-4‰, and more preferably 4‰.

[0050] In the present invention, the rotation speed of the mixing and grinding in step (3) is preferably 300 to 600 r / min, more preferably 380 to 500 r / min, and more preferably 480 r / min.

[0051] In the present invention, the mixing and grinding time in step (3) is preferably 1 to 3 hours, more preferably 1.7 to 2.5 hours, and more preferably 2 hours.

[0052] In the present invention, the temperature of the mixed grinding in step (3) is preferably 80-90°C, more preferably 83-88°C, and more preferably 85°C.

[0053] The invention also provides a method for preparing a black talc whitening composite powder and a black talc whitening composite powder obtained.

[0054] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Example 1

[0056] This embodiment provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0057] (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then sent to a 198-type ring roller mill for dry grinding to obtain 400-mesh black talc powder;

[0058] (2) Wet grinding: 400 mesh black talc powder was mixed with water to prepare a powder slurry with a solid content of 60%, and the powder slurry was mixed with a composite grinding aid of polyethylene glycol (3‰ of the mass of the black talc powder) and calcium lignin sulfonate (4‰ of the mass of the black talc powder), and a composite dispersant of sodium methylene dinaphthalene sulfonate (4‰ of the mass of the black talc powder) and sodium dodecylbenzene sulfonate (3‰ of the mass of the black talc powder), and then sent to a 3600L vertical stirred mill for constant temperature wet grinding at 80°C, with a stirring speed of 2500 r / min and a grinding time of 2 h to obtain a 5000 mesh black talc slurry;

[0059] (3) Mechanochemical coating: 5000 mesh black talc slurry was mixed and ground with 30% solid content and titanium dioxide slurry with an average particle size of 0.2 μm, the mass ratio of titanium dioxide slurry to black talc slurry was 1:30, and a mixed flocculant with a total amount of 2‰ of the mass of titanium dioxide powder and a mass ratio of polyacrylamide and sodium polystyrene sulfonate of 1:1 was added, and liquid phase mechanochemical coating was carried out at 80°C, the stirring speed of grinding was 400 r / min, and the grinding time was 2 h to obtain a core-shell composite slurry;

[0060] (4) Post-treatment: The core-shell composite slurry was flash dried, depolymerized, collected in bags, and packaged as a finished product to obtain a black talc whitening composite powder. The performance test results are shown in Table 1.

[0061] Table 1. Properties of 5 batches of black talc whitening composite powder obtained in Example 1

[0062]

[0063] Example 2

[0064] This embodiment provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0065] (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then sent to a 198-type ring roller mill for dry grinding to obtain 400-mesh black talc powder;

[0066] (2) Wet grinding: 400 mesh black talc powder was mixed with water to prepare a powder slurry with a solid content of 65%, and the powder slurry was mixed with a composite grinding aid of polyethylene glycol (4‰ of the mass of the black talc powder) and calcium lignin sulfonate (5‰ of the mass of the black talc powder), and a composite dispersant of sodium methylene dinaphthalene sulfonate (5‰ of the mass of the black talc powder) and sodium dodecylbenzene sulfonate (4‰ of the mass of the black talc powder), and then sent to a 3600L vertical stirred mill for constant temperature wet grinding at 80°C, with a stirring speed of 2500 r / min and a grinding time of 2 h to obtain a 5000 mesh black talc slurry;

[0067] (3) Mechanochemical coating: 5000 mesh black talc slurry was mixed and ground with titanium dioxide slurry with a solid content of 35% and an average particle size of 0.2 μm, the mass ratio of titanium dioxide slurry to black talc slurry was 1:40, and a mixed flocculant with a total amount of 3‰ of the mass of titanium dioxide powder and a mass ratio of polyacrylamide and sodium polystyrene sulfonate of 1:1 was added, and liquid phase mechanochemical coating was carried out at 80°C, the stirring speed of grinding was 600 r / min, and the grinding time was 2 h to obtain a core-shell composite slurry;

[0068] (4) Post-treatment: The core-shell composite slurry was flash dried, depolymerized, collected in bags, and packaged as a finished product to obtain a black talc whitening composite powder. The performance test results are shown in Table 2.

[0069] Table 2. Properties of 5 batches of black talc whitening composite powder obtained in Example 2

[0070]

[0071] Example 3

[0072] This embodiment provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0073] (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then sent to a 198-type ring roller mill for dry grinding to obtain 400-mesh black talc powder;

[0074] (2) Wet grinding: 400 mesh black talc powder was mixed with water to prepare a powder slurry with a solid content of 70%, and the powder slurry was mixed with a composite grinding aid of polyethylene glycol (5‰ of the mass of the black talc powder) and calcium lignin sulfonate (6‰ of the mass of the black talc powder), and a composite dispersant of sodium methylene dinaphthalene sulfonate (6‰ of the mass of the black talc powder) and sodium dodecylbenzene sulfonate (5‰ of the mass of the black talc powder), and then sent to a 3600L vertical stirred mill for constant temperature wet grinding at 80°C, with a stirring speed of 2500 r / min and a grinding time of 2 h to obtain a 5000 mesh black talc slurry;

[0075] (3) Mechanochemical coating: 5000 mesh black talc slurry was mixed and ground with titanium dioxide slurry with a solid content of 40% and an average particle size of 0.2 μm, with the mass ratio of titanium dioxide slurry to black talc slurry being 1:50, and a mixed flocculant with a total amount of 4‰ of the mass of titanium dioxide powder and a mass ratio of polyacrylamide and sodium polystyrene sulfonate of 1:1 was added, and liquid phase mechanochemical coating was carried out at 90°C, the stirring speed of grinding was 500 r / min, and the grinding time was 2 h to obtain a core-shell composite slurry;

[0076] (4) Post-treatment: The core-shell composite slurry was flash dried, depolymerized, collected in bags, and packaged as a finished product to obtain a black talc whitening composite powder. The performance test results are shown in Table 3.

[0077] Table 3. Properties of 5 batches of black talc whitening composite powder obtained in Example 3

[0078]

[0079] Comparative Example 1

[0080] This comparative example provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0081] (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then sent to a 198-type ring roller mill for dry grinding to obtain 400-mesh black talc powder;

[0082] (2) Wet grinding: 400 mesh black talc powder was mixed with water to prepare a powder slurry with a solid content of 65%, and the powder slurry was mixed with a composite grinding aid of polyethylene glycol (4‰ of the mass of the black talc powder) and calcium lignin sulfonate (5‰ of the mass of the black talc powder), and a composite dispersant of sodium methylene dinaphthalene sulfonate (5‰ of the mass of the black talc powder) and sodium dodecylbenzene sulfonate (4‰ of the mass of the black talc powder), and then sent to a 3600L vertical stirred mill for constant temperature wet grinding at 80°C, with a stirring speed of 2500 r / min and a grinding time of 2 h to obtain a 5000 mesh black talc slurry;

[0083] (3) Blending: The 5000 mesh black talc slurry was dried, depolymerized, and collected to obtain a black talc ultrafine powder. Finally, the obtained black talc ultrafine powder was mixed with titanium dioxide powder with an average particle size of 0.2 μm (the mass ratio of black talc ultrafine powder to titanium dioxide powder was 40:1) at a high mixing speed of 600 r / min for 30 min to obtain a composite powder of black talc powder and titanium dioxide powder. The performance test results are shown in Table 4.

[0084] Table 4. Properties of 5 batches of composite powders of black talc and titanium dioxide powder obtained in Comparative Example 1

[0085]

[0086]

[0087] Comparative Example 2

[0088] This comparative example provides a method for preparing a black talc whitening composite powder, comprising the following steps:

[0089] (1) Grinding and calcining: The black talc ore is crushed and ground to obtain 400 mesh black talc powder, which is then calcined at 1300°C for 2 hours;

[0090] (2) Wet grinding: The calcined black talc powder was mixed with water to prepare a powder slurry with a solid content of 65%, and the powder slurry was mixed with a composite grinding aid of polyethylene glycol (4‰ of the mass of the black talc powder) and calcium lignin sulfonate (5‰ of the mass of the black talc powder), and a composite dispersant of sodium methylene dinaphthalene sulfonate (5‰ of the mass of the black talc powder) and sodium dodecylbenzene sulfonate (4‰ of the mass of the black talc powder), and then sent to a 3600L vertical stirred mill for constant temperature wet grinding at 80°C, with a stirring speed of 2500r / min and a grinding time of 2h to obtain a 5000 mesh black talc slurry;

[0091] (3) Post-treatment: The black talc slurry was dried, depolymerized, dispersed and collected to obtain ultrafine black talc powder. The performance test results are shown in Table 5.

[0092] Table 5. Properties of 5 batches of ultrafine black talc powder obtained in Comparative Example 2

[0093]

[0094] It can be seen from the test results of Example 2 and Comparative Example 1 that there is a mechanochemical effect between the black talc powder and the titanium dioxide powder, which significantly improves the whiteness and is more conducive to its application in the field of materials with requirements on color.

[0095] It can be seen from the test results of Example 2 and Comparative Example 2 that the whiteness of the black talc whitening composite powder prepared by the method of the present invention is higher than the whiteness of the black talc calcined at 1300°C in the prior art, indicating that the method provided by the present invention has a better whitening effect and further expands the application range of black talc.

[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a black talc whitening composite powder, characterized in that: The following steps are involved: (1) Crushing and dry grinding: The black talc ore is coarsely crushed, cleaned, crushed once, crushed twice, and then dry ground to obtain black talc powder; (2) Wet grinding: black talc powder is mixed with water to prepare a powder slurry with a solid content of 60-70%; the powder slurry is mixed with a grinding aid and a dispersant and then wet-grinded at a constant temperature to obtain a black talc slurry of 5000 mesh; (3) Mechanochemical coating: 5000 mesh black talc slurry, titanium dioxide slurry and flocculant were mixed and ground, and liquid phase mechanochemical coating was performed to obtain a core-shell composite slurry; (4) Post-treatment: The core-shell composite slurry is flash dried, depolymerized and dispersed to obtain a black talc whitening composite powder; Wherein, in step (3), the average particle size of the titanium dioxide powder in the titanium dioxide slurry is 0.1 to 0.3 μm, and the mass ratio of the titanium dioxide slurry to the black talc slurry is 1:30 to 50; In step (3), the flocculant is a mixture of polyacrylamide and sodium polystyrene sulfonate, the mass ratio of polyacrylamide to sodium polystyrene sulfonate is 0.8-1.2:1, and the amount of the flocculant is 2-4‰ of the mass of titanium dioxide in the titanium dioxide slurry.

2. The method for preparing a black talc whitening composite powder according to claim 1, characterized in that: In step (2), the grinding aid is a mixture of polyethylene glycol and calcium lignin sulfonate, the amount of polyethylene glycol is 3-5‰ of the mass of the black talc powder, and the amount of calcium lignin sulfonate is 4-6‰ of the mass of the black talc powder.

3. The method for preparing a black talc whitening composite powder according to claim 2, characterized in that: In step (2), the dispersant is a mixture of sodium methylene dinaphthalene sulfonate and sodium dodecylbenzene sulfonate, the amount of sodium methylene dinaphthalene sulfonate is 4-6‰ of the mass of the black talc powder, and the amount of sodium dodecylbenzene sulfonate is 3-5‰ of the mass of the black talc powder.

4. The method for preparing a black talc whitening composite powder according to claim 2 or 3, characterized in that: In step (2), the rotation speed of the constant temperature wet grinding is 2500-3000 r / min, the time of the constant temperature wet grinding is 1-3 hours, and the temperature of the constant temperature wet grinding is 70-80°C.

5. The method for preparing a black talc whitening composite powder according to claim 4, characterized in that: In step (3), the solid content of the titanium dioxide slurry is 30-40%.

6. The method for preparing a black talc whitening composite powder according to claim 2 or 5, characterized in that: In step (3), the rotation speed of the mixed grinding is 300-600 r / min, the time of the mixed grinding is 1-3 h, and the temperature of the mixed grinding is 80-90° C.

7. The black talc whitening composite powder obtained by the method for preparing the black talc whitening composite powder according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method of whitening black talc

    CN101519305A

  • Black talc-based composite white pigment preparation method

    CN106398322A